PENGARUH PRENATAL MASSAGE TERHADAP PENURUNAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI PMB WILAYAH KERJA PUSKESMAS UJUNG GADING TAHUN 2023 - Nanda Oktavia, Sesmi; Larasati, Timmy (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Back pain is one of the discomforts of pregnancy because it can interfere with the activities of pregnant women. Treatment for back pain in pregnancy can include pharmacology and non-pharmacology. One of the non-pharmacological treatments for back pain in pregnant women is Prenatal Massage. This study aims to determine the effect of Prenatal Massage on reducing back pain in third trimester pregnant women in the PMB Working Area of the Ujung Gading Community Health Center. This type of research is experimental with a pretest - posttest one group design. The population in this study was all third trimester pregnant women in the PMB Ujung Gading Community Health Center Working Area, totaling 15 pregnant women. The research sample was 15 pregnant women taken by total sampling. The results of the study showed that before prenatal massage, the pain experienced by pregnant women according to the NRS (Numeric Rating Scales) was 0 (0%), mild pain 2 (13%), moderate pain 7 (47%), severe pain 5 (33%) , and very severe pain 1 (7%). And after prenatal massage, the results were 2 (13%) without pain, 10 (67%) with mild pain, 3 (20%) with moderate pain, 0 (0%) with severe pain, and 0 (0%) with very severe pain. Parametric statistical test, namely Paired Sample T-test which shows P-Value = 0.000 < (0.05) so Ha is accepted. The conclusion of this research is that there is an effect of prenatal massage on reducing back pain in pregnant women in the third trimester in the PMB working area of the Ujung Gading Community Health Center.Keywords: Third Trimester Pregnant Women, Prenatal Massage, Back Pain.